Firm Performance: A Panel Study on the Indonesian Food and Beverage Industry - Michael, Michael; Widjaja, William; Simon, Febryanti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine how human capital efficiency, structural capital, and capital employed affect the business performance of companies in Indonesia’s food and beverage sector. Methodology/approach: The research was conducted using secondary data collected from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange for the years 2018-2022. The data analysis was carried out using panel data regression and hypothesis testing with EViews software version 12. Results and Findings: The results show that both human capital efficiency and structural capital have a significant impact on business performance. However, capital employed efficiency does not have a significant effect. Human and structural capital are found to contribute positively to innovation, productivity, and competitive advantage. Conclusions: This study shows that the efficiency of human resources has a positive effect on the performance of companies in the Indonesian food and beverage industry, while the efficiency of capital use is not significant, so it is important for companies and the government to focus on developing human resources, innovation, and more optimal capital management. Limitations: The study is limited to publicly listed food and beverage companies in Indonesia and relies solely on financial data, without incorporating qualitative or industry-specific operational factors. Contribution: This study makes a significant contribution to the field of strategic management and intellectual capital by providing empirical evidence that both human and structural capital are vital to business performance. It offers practical insights for company managers, policymakers, and researchers interested in enhancing firm value through human capital investment and capital efficiency.